Effect of standard heat treatment on tensile and creep properties of Inconel 718 - O., Bapokutty; A.R., Said; Syarif Junaidi, S Djalil; Zainuddin, Sajuri (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.